Diretrizes para o desenvolvimento de empreendimentos do tipo Student Housing: análise dos novos produtos e necessidades dos estudantes - Muller, Hyago Maurício Bremm (2020)
Student housing was discussed in the literature under the aspects of residential preference and satisfaction; inducing factors of behavior and demand in the real estate market; and influencing variables in choosing the habitation. However, the works that approach topics about real estate meant for students and the new products of the Brazilian real estate market, specifically the ones named Student Housing, are scarce. The problems related to the supply of real estate meant for students in Brazil, mainly in university towns, are directly linked to the low quality of the built environment and the absence of researches that identify the students’ needs. As a solution, there is the Student Housing model, which emerges in an innovative way, once it is concerned about the quality of the built environment, offers equipped and furnished rooms, presents a diversity of services and conveniences, and also provides a complete internal infrastructure for studies, physical activities, leisure and entertainment. However, in order to become competitive in the Real Estate sector, being able to generate income and keep it viable during the operation period, innovating is not enough, it is necessary to capture value, identifying which factors are really important for the target audience. In this context, the present work proposed, initially, through a comparative study of seven Student Housing real states, to investigate the main characteristics of this product model. Such information, added to the bibliographic review of the literature, allowed the exploration, through a survey, of university students’ opinion about the importance of four preestablished requirements (rent, location, services and facilities, and project). Moreover, the preference in the choice for a housing unit through the conjoint analysis technique was also examined, a technique used to correlate typology, number of occupants, and rent prices. The results pointed out that students consider it is very important that their habitations are located near the higher education institution and supermarkets, and present easy access to public transportation. They also indicated that the real estates must offer flexible (shorter) rental agreements; no guarantor/security deposit, a single bill (all inclusive) and also common areas which meet their needs, such as: study room; gym/fitness area; areas for parties with barbecue grills; social area/solarium/garden; private areas with individual bedrooms and bathrooms; private dining room/kitchen with furniture and equipment (kitchenware and appliances). Other important factors are the offer of Wi-Fi internet services in the unit (private area); reception (24/7); cleaning and maintenance of the unit (private area); minimarket/snacks; laundry services; and photocopies and printing services. Finally, the results of the conjoint analysis showed typology as the most important attribute compared to the number of occupants and rent price. Moreover, the results also showed that there is a higher attractiveness for one type of housing unit: standard apartments, projected for individual occupation and with a rent price interval ranging from R$1.100,00 to R$1.700,00. Based on that, fourteen guidelines were suggested to orient the student real estate market agents in the development of their products.